Profiles of mental well- and ill-being among elite athletes: associations with sport-related demands and resources - Kaski, S.; Arvinen-Barrow, M.; Kinnunen, U.; Parkkari, J. (Journal of Clinical Sport Psychology, 2024)
The aim of the present study was to identify profiles of elite athlete mental well- and ill-being and study how the profiles (i.e., subgroups of athletes) differed in sport-related demands and resources. A total of 259 Finnish elite athletes (n = 170 active and n = 89 retired) completed quantitative self-report inventories. Through cluster analysis, four profiles of mental well- and ill-being were identified. Profile 1 was overrepresented by retired, older, and male athletes, and characterized by good mental well-being. Profile 2 consisted mainly of active athletes who reported mild risk for alcohol abuse. Profile 3 consisted mainly of women who displayed possible presence of an eating disorder. Profile 4 was typical of young athletes with mental ill-being. The balance between sport-related demands and resources appeared to be the healthiest in Profile 1 and worst in Profile 4. The present findings are beneficial for those who work with and/or provide psychological support to athletes.